Observational study of prehospital delays in patients with chest pain. Issue 3 (1st May 2003) - Hitchcock, T; Rossouw, F; McCoubrie, D; Meek, S
Abstract : Objective: To define and measure patient reported prehospital delay in presentation to the emergency department with chest pain and identify simple strategies that may reduce this delay. The authors investigated the null hypothesis that the patients choice of service to call for acute medical help has no effect on the timing of thrombolysis. Method: A prospective observational study of prehospital times and events was undertaken on a target population of patients presenting with acute chest pain attributable to an acute coronary syndrome over a three month period. Results: Patients who decided to call the ambulance service were compared with patients who contacted any other service. Most patients who contact non-ambulance services are seen by general practitioners. The prehospital system time for 121 patients who chose to call the ambulance service first was significantly shorter than for 96 patients who chose to call another service (median 57 min v 107 min; p<0.001). Of the 42 patients thrombolysed in the emergency department, those who chose to call the ambulance service had significantly shorter prehospital system times (number 21 v 21; median 44 v 69 min; p<0.001). Overall time from pain onset to initiation of thrombolysis was significantly longer in the group of patients who called a non-ambulance service first (median 130 min v 248 min; p=0.005). Conclusions: Patient with acute ischaemic chest pain who call their general practice instead of the ambulance service are likely to have delayed thrombolysis. This is likely to result in increased mortality. The most beneficial current approach is for general practices to divert all patients with possible ischaemic chest pain onset within 12 hours direct to the ambulance service.